Voice through ballot : election and people's perception - Ahmad, Mohiuddin, 1952-; Community Development Library (Dhaka, Bangladesh) (Dhaka : Community Development Library, 2001)
Study conducted by Community Development Library, Dhaka, Bangladesh.
Includes statistical tables.
Keywords: Elections -- Bangladesh; Bangladesh -- Politics and government -- 1971-